Hubungan Beban Kerja dengan Stres Kerja pada Perawat di Ruang Instalasi Rawat Inap Bedah di RSUP M. Djamil Padang Tahun 2022 - Mindayani, Sri; Aisyiah, Intan Kamala; Safutri, Shinta Okvianti (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2023)
The results of a survey conducted by the Indonesian National Nurses Association (PPNI) in 2018 about 50.9% of nurses in Indonesia experience work stress. RSUP Dr. M. Djamil Padang is a referral hospital for the Central Sumatra region, serving people in the provinces of West Sumatra, Riau, Jambi, Bengkulu, and the southern part of North Sumatra. IRNA surgery at RSUP Dr. M. Djamil Padang has 180 patient beds. In the initial survey conducted by researchers, some nurses experienced symptoms of work stress such as feeling tired, dizzy, irritable, no appetite, exhausted. The purpose of this study was to determine the relationship between workload and tenure with work stress on nurses in IRNA surgery at RSUP Dr. M. Djamil Padang in 2022. The type of research used is quantitative with a cross sectional design. The study was conducted from January to August 2022 on surgical IRNA nurses at RSUP Dr. M. Djamil Padang. The population in this study amounted to 87 nurses, using a total sampling technique with inclusion and exclusion criteria. Data processing using SPSS. The research instrument used a questionnaire. The analysis used is univariate and bivariate analysis with Chi-Square test. The results showed that 51.8% of nurses experienced work stress, 56.5% of nurses had a heavy workload and 54.1% of nurses with a working period of > 5 years. The results of the bivariate analysis showed that there was a relationship between workload (P-value = 0.04) and length of service (P-value = 0.02) with work stress on nurses at IRNA surgical Dr. M. Djamil Padang in 2022. It is hoped that the agency should hold training on stress management for nurses as well as activities such as outbound, study tours, spiritual activities, and doing physical activities together such as gymnastics for refreshment and refreshing for nurses.